2012
DOI: 10.1088/0953-2048/26/2/025010
|View full text |Cite
|
Sign up to set email alerts
|

High-TcJosephson junctions fabricated by focused ion beam direct milling

Abstract: High-T c Josephson junctions were successfully fabricated by focused ion beam (FIB) direct milling. The characteristics of the junction barrier were carefully controlled by tuning the thickness of the link region. The optimal remaining thickness for the YBCO is about 70-80 nm even though the YBCO thicknesses are different. The temperature-dependence of the critical current provides good evidence of the superconductor-normal-superconductor weak link of the junctions. Although the flux-flow behavior increasingly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Three-dimensional images of the first and last trenches are shown in Figure 1 (b) and (c). The wedge shaped profile of the p ≈ 0.121 trench is very similar to that obtained by [8] on an optimally doped (p ≈ 0.167) film. The next trench, with p ≈ 0.122, also exhibits a wedge shape and a nearly identical depth (≈ 300 nm), however, the width of the trench has been reduced by ≈ 1/3.…”
Section: Results and Analysissupporting
confidence: 76%
See 3 more Smart Citations
“…Three-dimensional images of the first and last trenches are shown in Figure 1 (b) and (c). The wedge shaped profile of the p ≈ 0.121 trench is very similar to that obtained by [8] on an optimally doped (p ≈ 0.167) film. The next trench, with p ≈ 0.122, also exhibits a wedge shape and a nearly identical depth (≈ 300 nm), however, the width of the trench has been reduced by ≈ 1/3.…”
Section: Results and Analysissupporting
confidence: 76%
“…Using this process would potentially result in a low cost method for producing devices having a higher density of Josephson junctions than by direct ion milling of an optimally doped film. Use of a gold over layer in the milling process will result in a narrowing of the milled section down to the order of 20 nm -50 nm, as demonstrated in [8]. Combined with the apparent ion beam confining effects of the well ordered Cu-O chain states (p = 1/8), arrays of Josephson junctions a few tens of coherence lengths apart (ξ ∼ 10Å) could be fabricated resulting in a density approaching 10 8 /cm 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently Wu et al, 6 using an optimally doped YBa 2 Cu 3 O 7−δ film (7 − δ ≈ 6.91), demonstrated that focused ion beam (FIB) milling can be used as a reliable method to produce HTS Josephson junctions. A gold top layer is deposited on the film having a thickness just less than the depth to which impacting gallium ions can penetrate.…”
Section: Introductionmentioning
confidence: 99%